Adsorption of reactive dyes from aqueous solutions by quaternized palm kernel shell - Koay, Yin Shin (2013)
Quaternized biomass serves as substitution to activated carbon as adsorbent to solve the issue on activated carbon such as cost, environment impact and sustainability. However, there is lack of research on reactive dyes adsorption by quaternized lignocellulosic fibers and none of research on quaternized PKS as adsorbent been reported up to date. Therefore, an attempt was made to chemically quaternized palm kernel shell (QPKS) as adsorbent to increase adsorption affinity towards two reactive dyes namely Reactive Black 5 (RB5) and Reactive Red E (RRE). Palm kernel shell (PKS) was quaternized successfully by treating with N-(3-chloro-2-hydroxypropyl) trimethylammonium chloride under basic condition. The QPKS was characterized by CHN elemental analysis, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Energy Dispersive X-Ray (EDX),Brunauer, Emmett and Teller (BET) analysis, Thermalgravimetric analysis (TGA) and X-Ray Diffraction analysis (XRD). Result from CHN and EDX elemental analysis demonstrated an increase of nitrogen percentage after treatment further support the success of the reaction. Surface characterization of QPKS by SEM and BET analysis confirmed the surface pore enlargement from mesopores to macropores after quaternization. Furthermore, chemical properties such as point zero charge,surface chemistry and chemical composition were determined. Point of zero charge of QPKS measured at 25 ˚C was at pH 2.2. Adsorption experiment was carried out to investigate the effect of pH, dosage of QPKS, initial concentration, contact time and temperature in single batch system with constant shaking rate of 160 rpm for both dyes. The optimum pH for removal of RB5 and RRE by QPKS was at pH4. 1.0 g/L of QPKS was chosen as the appropriate dosage for both dyes adsorption. Four analytical isotherm equations, Langmuir,Freundlich, Sips and Redlich-Peterson models were fitted to the equilibrium adsorption data. The Redlich-Peterson model is best fitted to the data. The maximum adsorption capacity of QPKS was found to be 191.2 mg/g for RB5 and 182.8 mg/g for RRE. The rate of adsorption in single system was found to agree with pseudosecond- order kinetics model. The adsorption of both dyes onto QPKS is spontaneous process and exothermic in nature. Hence increase in adsorption temperature does not favor the process. For binary system, an artificial neural network (ANN) model was developed to stimulate the adsorption of RB5 and RRE by QPKS under varying parameters such as pH, dosage and dye concentration. Regeneration of QPKS was carried out by shaking the used QPKS in 0.1M NaOH solution. Regeneration of QPKS for adsorption of RB5 was valid but not for RRE. In conclusion, the QPKS synthesized was proven able in removing RB5 and RRE dye in aqueous solution.